And challenges surrounding the full inclusion of women in democratic theories and practices A comparative study of the transitions in Latin America and the north of Africa from a perspective south - south (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
Riots and political changes taking place in North Africa since 2011 highli- ght the categories of democracy and democratization together with the challenge of addressing them with their specificities, taking into account not only the formal aspects but also whether they are based on popu- lar representation and the deepening of democratic institutions, gender equality and human rights. The main aims of this work are to analyze and to compare the emer- gence of political identities, the situation of  women’s rights and the agendas around the processes that are developing in Tunisia and Egypt to compare them with the with the transition processes in three Latin American countries: Argentina, Chile and Brazil. We base the analysis on a south-south perspective and the critical approach derived from the theory of hegemony on the current conceptualizations of democracy and democratization, mostly of liberal stamp. Our methodology includes conducting interviews with activists and scholars from the countries concerned, performing observational work, reviewing literature and monitoring of Internet news.
Keywords: Democracies; democratization; gender equality; human rights.